Research on the Path of Building Talent Cultivation Ecosystem of Applied Undergraduate Colleges and Universities： Taking Yangzhou University Guangling College Clothing and Dress Design as an Example - Jinchao ZHOU; Fayuan MAI; Jiajue SUN; Tianyao LIU (Pige Kexue Yu Gongcheng)
With the evolution of industrial upgrading and market demand, the traditional education model reveals the problem of disconnection with actual demand. Focusing on the challenges faced by applied undergraduate colleges and universities in China in the cultivation of talents specialized in apparel and clothing design, and taking Yangzhou University's Guangling College as an example, this article analyzed in depth the problems that exist in professional education, including the disconnection between theory and practice, the insufficiency of faculty, the lagging behind of teaching content, the lack of supporting resources, the singularity of the evaluation system, and the lack of clarity in the employment destinations of the graduates. It is pointed out that although applied education has significant advantages in cultivating technical and skilled talents, the existing model fails to fully meet the industry's demand for high-quality talents. It is emphasized that colleges and universities should work closely with enterprises to provide students with learning opportunities that are in line with the actual working environment, and give more support in career guidance and market interface. By implementing these strategies, the employment competitiveness of students can be improved, while the development of local industries can be promoted, and more high-quality applied talents can be cultivated for the society.